Methylmercury-induced developmental toxicity is associated with oxidative stress and cofilin phosphorylation. Cellular and human studies - Caballero, Beatriz (2017)
Environmental exposure to methylmercury (MeHg) during development is of concern because it is easily incorporated in children's body both pre- and post-natal, it acts at several levels of neural pathways (mitochondria, cytoskeleton, neurotransmission) and it causes behavioral impairment in child. We evaluated the effects of prolonged exposure to 10–600 nM MeHg on primary cultures of mouse cortical (CCN) and of cerebellar granule cells (CGC) during their differentiation period. In addition, it was studied if prenatal MeHg exposure correlated with altered antioxidant defenses and cofilin phosphorylation in human placentas (n = 12) from the INMA cohort (Spain). Exposure to MeHg for 9 days in vitro (DIV) resulted in protein carbonylation and in cell death at concentrations ≥200 nM and ≥300 nM, respectively. Exposure of CCN and CGC to non-cytotoxic MeHg concentrations for 5 DIV induced an early concentration-dependent decrease in cofilin phosphorylation. Furthermore, in both cell types actin was translocated from the cytosol to the mitochondria whereas cofilin translocation was found only in CGC. Translocation of cofilin and actin to mitochondria in CGC occurred from 30 nM MeHg onwards. We also found an increased expression of cortactin and LIMK1 mRNA in CGC but not in CCN. All these effects were prevented by the antioxidant probucol. Cofilin phosphorylation was significantly decreased and a trend for decreased activity of glutathione reductase and glutathione peroxidase was found in the fetal side of human placental samples from the highest (20–40 μg/L) MeHg-exposed group when compared with the low (<7 μg/L) MeHg-exposed group. In summary, cofilin dephosphorylation and oxidative stress are hallmarks of MeHg exposure in both experimental and human systems.